Interioridade e exterioridade : um estudo da obra A subida do Monte Carmelo de João da Cruz - Sanson Junior, Jacir Silvio (2016)
It undertakes a study on the subject of interiority in the book Ascent of Mount Carmel. It is noticeable that John of the Cross works to a conceptual reworking. He makes several criticisms about practices and teachings of that time in his immediate surroundings, which are recorded to the effect of promoting an itinerary explained by the symbolic of a night climbing. The theoretical categories that support his formulation carry articulations that we explicit in terms of the interiority-exteriority binomial. Relations that are constitutive, taking into account a developed hermeneutic line for reading the writings, reverberate in anthropological analysis about the three faculties of the soul and its links with the theological virtues. The author explores several points that are located in the heritage of a mystical tradition, and dialogues with different epistemological bases in the history of theology and philosophy. In function of reliefs that distinguish their originality traits, we conclude that there is a Juancrucian’s conception of interiority.